Application of multistage evolutionary programming for reactive power control in power system / Noor Azmi Mohd. Radzi - Mohd. Radzi, Noor Azmi (2006)
This final year project discussed the application of multistage evolutionary programming for reactive power dispatch in power system. Several techniques have been developed to make the EP suitable to the practical optimal problems of large scale systems. Simulation results are presented to show the potential for applications of the proposed method to power system economical and secure operations. Distribution system through network reconfiguration is realized to be operated under minimized loss condition due to a large consumption in power energy nowadays. This final year project presents a technique for networks reconfiguration that aims to improve voltage stability and hence minimized the loss. By presenting the relationship between voltage stability and loss minimization it can be shown that voltage stability is maximized when power losses are minimized in the network. Simulation studies on IEEE 30-bus Reliability Test System (RTS) are presented to illustrate the methodology and to demonstrate the benefits of the proposed method using MATLAB programming language.